(untitled) (London Journal of Medical and Health Research, 2025)
Introduction: Liposuction is the most commonly performed plastic surgery, aimed at improving both the physical appearance of patients and their self-esteem. However, like any surgical intervention, it can present complications. One of the most frequent is contour irregularity, which, although not usually severe, has both physiological and aesthetic implications for the patient. Objective: The general objective of the research is to observe the histological and clinical changes in the abdominal skin of five women who developed fibrosis as a complication of an abdominal liposuction performed more than two years ago, following a single application of recombinant enzymes. This will be done by describing these changes, analyzing the relationship between clinical and histological findings, and comparing the results before and after the enzyme application. Methods: The study is a descriptive longitudinal one, conducted on 5 women between the ages of 33 and 60 with post-liposuction fibrosis, without previous treatments except for massages and radiofrequency. The cases were selected through simple random sampling. Both photographic records and biopsies were taken before and after the enzyme application. Results: The results showed significant clinical improvement in skin quality and texture, with a reduction in lumpiness and contour regularization. Histologically, a decrease in collagen basophilia and inflammatory response was observed, as well as a decrease in fragmented elastic fibers and an increase in intact elastic fibers. Regarding collagen fibers, greater integrity and homogeneity were noted. Conclusion: The application of recombinant enzymes resulted in significant clinical and histological improvements. This treatment proved to be safe, reliable, and easy to apply, with high patient satisfaction, suggesting its potential to replace more invasive treatments in the management of post-liposuction fibrosis.